(untitled) (Social Science Review, 2026)
This study examines Anya Jibon (1995), a film depicting the struggles of loom weavers in rural Bangladesh during the political and economic shifts of the early 1990s. Employing a few non- conventional styles, the film unveils the life and struggle of lower-class communities, highlights social inequality and political issues, and aims to raise awareness and drive actions to change. Employing the Third Cinema theory, this study analyzes how Anya Jibon stands apart from mainstream Bangladeshi films in both its themes and styles, presenting itself as a tool for socio- political commentary. Through a textual analysis of the film’s narrative and formal aspects, the study finds that Anya Jibon crafts an intriguing portrait of the then socio-political landscape by transforming the traditional film techniques and critiques the existing social inequality and political oppression intending to make audiences conscious and critical about the happenings surrounding them. Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 117-136